Age-, Sex-, and Puberty-Associated Reference Intervals for Lipid Profile in Iranian Children and Adolescents. (24th February 2023) - Montazeri-Najafabady, Nima; Dabbaghmanesh, Mohammad Hossein; Asmarian, Naeimehossadat; Rais Pour, Homeyra
Abstract : Childhood dyslipidemia is considered a major worldwide health issue. Identification of children with dyslipidemia is notably essential for healthcare providers in establishing and releasing recommendations for the management and prevention of future CVD. In the present study, we provided reference values for the lipid profile from Kawar (a city in the south of Iran) cohort of healthy children and adolescents aged 9–18 years. 472 subjects (234 girls and 238 boys) contributed to the current prospective cohort study using a systematic random sample stratified by age. Fasting lipid levels were measured by enzymatic reagents. Dual-energyX-ray absorptiometry (DEXA) was used to evaluate puberty based on the Tanner stages. LMS Chart Maker and Excel software were used to construct the gender-specific reference plots showing the 3, 10, 25, 50, 75, 90, and 97th percentiles of BMI, cholesterol, TG, HDL, TC, LDL, and non-HDL. The outcomes revealed that concentrations of TC, LDL, and non-HDL were drastically greater in girls as compared to boys. TG increased with age in both genders, while HDL, TC, LDL, and non-HDL declined. We also observed that puberty was associated with higher lipid values in boys and girls except for TG in boys. Our study prepared age- and sex-specific reference intervals for the lipid profile in Iranian children and adolescents. Converted to age and gender percentiles, these reference intervals are expected to serve as an effective and consistent tool for doctors to identify dyslipidemia among children and adolescents.